Immobilization of an Iridium Pincer Complex in a Microporous Polymer for Application in Room‐Temperature Gas Phase Catalysis. Issue 45 (31st August 2020) - König, Michaela; Rigo, Massimo; Chaoui, Nicolas; Tran Ngoc, Trung; Epping, Jan Dirk; Schmidt, Johannes; Pachfule, Pradip; Ye, Meng‐Yang; Trunk, Matthias; Teichert, Johannes F.; Drieß, Matthias; Thomas, Arne
Abstract: An iridium dihydride pincer complex [IrH2 (POCOP)] is immobilized in a hydroxy‐functionalized microporous polymer network using the concepts of surface organometallic chemistry. The introduction of this novel, truly innocent support with remote OH‐groups enables the formation of isolated active metal sites embedded in a chemically robust and highly inert environment. The catalyst maintained high porosity and without prior activation exhibited efficacy in the gas phase hydrogenation of ethene and propene at room temperature and low pressure. The catalyst can be recycled for at least four times. Abstract : An iridium pincer complex, immobilized in a microporous polymer network, has been used as an efficient and recyclable catalyst for the gas phase hydrogenation of ethene and propene at room temperature and low pressure.